Perampasan Ruang Hidup Masyarakat Hukum Adat: Tantangan dan Harapan dalam Keadilan Agraria di Indonesia - Dian Maharani, Justhine; Nizam Zakka Arrizal (UIR Press, 2025)
The seizure of living space of indigenous peoples in Indonesia is a crucial issue that reflects the inequality in the management of agrarian resources. This phenomenon is often triggered by conflicts of interest between indigenous peoples, the government, and corporations, which results in the loss of indigenous peoples' access to land and natural resources, and threatens their cultural, social, and environmental sustainability. This article discusses the main challenges in efforts to realize agrarian justice, including weak recognition of customary rights, overlapping regulations, and minimal participation of indigenous peoples in decision-making. In addition, this article explores the hopes that can be realized through equitable agrarian reform policies, such as strengthening regulations, accelerating the recognition of customary land rights, strict law enforcement, and active involvement of indigenous peoples in the management of agrarian resources. By integrating an inclusive approach and the principle of sustainability, agrarian justice in Indonesia can be achieved, not only to protect the rights of indigenous peoples, but also to create harmony between economic development and environmental sustainability.